1991
DOI: 10.1152/ajpheart.1991.260.4.h1224
|View full text |Cite
|
Sign up to set email alerts
|

Regional deformation and contractile function in canine right ventricular free wall

Abstract: We used biplane cinefluorgraphy to study the regional deformation and local contractile function of the canine right ventricular free wall (RVFW) among the inflow, midventricular, and outflow regions. For a region delimited by three neighboring markers, under the assumption of homogeneous deformation, we identified the magnitudes and directions of principal shortening or elongation and changes in area every 16.7 ms. Furthermore, we extended this approach to study the alterations of these parameters during RV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
30
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 0 publications
10
30
0
Order By: Relevance
“…The amount of maximum strain measured (on average about 17%) was similar to previously measured RV strains in the conscious dog, 3,18,23 despite the substantially slowed heart rate in the anesthetized mouse in this study (250 bpm) compared with a conscious mouse (500-600 bpm). The literature contains conflicting results regarding regional strain differences.…”
Section: Regional Systolic Functionsupporting
confidence: 86%
See 1 more Smart Citation
“…The amount of maximum strain measured (on average about 17%) was similar to previously measured RV strains in the conscious dog, 3,18,23 despite the substantially slowed heart rate in the anesthetized mouse in this study (250 bpm) compared with a conscious mouse (500-600 bpm). The literature contains conflicting results regarding regional strain differences.…”
Section: Regional Systolic Functionsupporting
confidence: 86%
“…The literature contains conflicting results regarding regional strain differences. We found that strains were somewhat lower in the sinus region than the outflow tract region, which is consistent with some previous studies, 3,21 but disagrees with others. 18,27 The reasons for these discrepancies are not clear, but are likely due to differences in preparation such as in marker placement and open-vs. closed-chest measurements.…”
Section: Regional Systolic Functionsupporting
confidence: 79%
“…One-dimensional relative motion data has been gathered by tracking pairs of radiopaque beads tracked with biplane cineradiography [30,51) or pairs of crystals with ultrasound [28]. By implanting several markers close together on the same ventricular surface (e.g., endocardium), researchers have been able to derive biaxial, or in-plane, deformations [17,6,341. The human RV has been studied using the noninvasive MRI tissue tagging method.…”
Section: Related Workmentioning
confidence: 99%
“…A potentially important means of detecting and evaluating RV dysfunction is to quantitatively analyze changes in its motion. However, because of its thin wall and asymmetric geometry, the normal three-dimensional (3-D) motion and deformation of the RV are not yet well understood.Early studies (4,5,14,19,20,24) used implanted radiopaque markers to provide limited knowledge about RV motion, mostly in animals. Recently, imaging modalities, such as echocardiography, computed tomography, and conventional magnetic resonance imaging (MRI), have provided a noninvasive means of studying the RV (3, 7, 12).…”
mentioning
confidence: 99%